Sum rules for the decay of 35-plet into decuplet plus octet - Zimerman, A. H.; Fagundes, H. V. (Springer Nature, 1966)
« Sum rules » for the decay of a SU 3 35-plet into decuplet plus octet are derived. The consequences of the application of Goldberger-Treiman relations are also considered. © 1966 Società Italiana di Fisica.